Pengaruh Efisiensi, Keamanan, Dan Kemudahan Bertransaksi Terhadap Minat Penggunaan Mobile Payment (Studi Kasus Pada Konsumen Shizuka Ms.Glow Store Di Kota Gajah) - Anggun Eri Fadilah; Nani Septiana; Kuncoro Budi Riyanto (Jurnal Manajemen DIVERSIFIKASI, 2025)
Technological advances have an impact on the business sector, one of which is payment transactions. Mobile payment is one of the breakthroughs in the business sector with online transactions. However, unfortunately, there are still many people who have little interest in using mobile payments. The aim of this research is to determine the influence of efficiency, security and convenience on consumers' interest in using mobile payments at the Shizuka Ms Glowstore, Gajah City. This research applies quantitative research methods. The research location is at the Shizuka Store, Kota Gajah. The population in this research are consumers or buyers at the Shizuka store. The research sample was taken by accidental sampling with a sample size of 68. The data collection technique used a questionnaire with Likert scoring 1-5. The data analysis technique uses multiple linear regression formulas, t-test, F-test, and determination test. The research results show that efficiency influences interest in using mobile payment at Shizuka Ms Glow Store. Transaction security influences interest in using mobile payments. Ease of transactions influences interest in using mobile payments. Efficiency, transaction security and ease of transactions have a significant influence on interest in using mobile payments.